Rational Liquidity Crises in the Sovereign Debt Market : In Search of a Theory - Detragiache, Enrica (Washington, D.C. : International Monetary Fund, 1996)
This paper studies under what circumstances creditworthy sovereign borrowers may be denied liquidity by rational creditors. It is shown that, when the creditor side of the market consists of many small investors there may be multiple rational expectations equilibria. In one equilibrium, creditors' pessimistic expectations about the borrower's creditworthiness become self-fulfilling, and the borrower experiences a liquidity crisis. Multiple equilibria can be avoided by marketing the loan appropriately or by developing a reputation for following good policies. Liquidity problems can also arise because of the temporary disruption of international bond markets due to events unrelated to the borrower's circumstances. Policies responses are discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet